Self‐Supported Gold‐Silk‐Chrysanthemum‐Like Superstructures Arrays Derived from Mn‐doped CoPS Nanowires with Superhydrophilic and Superaerophobic Surface for Enhanced Oxygen Evolution. Issue 17 (11th May 2022) - Fan, Jiayao; Chen, Mingyu; Liu, Bingxue; Xu, Dongdong; Lin, Yue; Shi, Naien; Liu, Ying; Dai, Zhihui; Bao, Jianchun; Han, Min; Huang, Wei
Abstract: Metal phosphosulfides (layered MPS3 or pyrite‐type MPS) nanostructures have emerged as promising active materials for optoelectronics, magnetism, energy storage, and catalysis. Despite great progress that has been achieved, controllable synthesis of cationic‐doped CoPS nanostructures or related superstructures arrays remains challenging, and their electrocatalytic applications toward oxygen evolution reaction (OER) are not explored. Herein, the self‐supported Mn‐doped CoPS nanowire‐based gold‐silk‐chrysanthemum‐like superstructures arrays on carbon cloth (CC) with variable Mn‐content (Mn‐CoPS‐ x %/CC) are fabricated by thermal conversion of MnCo‐layered‐double‐hydroxides‐x%/CC precursors under P x S y vapor/Ar atmosphere. Compared with pure CoPS/CC, all the Mn‐CoPS‐ x %/CC show greatly enhanced electrocatalytic OER activity. Due to the suited Mn‐doping content and unique microstructure‐induced superhydrophilic and superaerophobic surface that can optimize electronic structure, offer more available active sites, and foster desorption of O2 product, the Mn‐CoPS‐5%/CC manifests the best OER activity with a low overpotential (270 mV) to reach 20 mA cm −2 current density and high turnover frequency (0.13 s −1 ), outperforming its counterparts, IrO2 /CC and most of recently reported OER catalysts. Moreover, such Mn‐CoPS‐5%/CC exhibits good catalytic stability. This work offers an efficient avenue for optimizing MPS nanostructures toward OER by combining doping and structure engineering strategies, and may promote their applications in water‐splitting or other clean energy options. Abstract : Self‐supported Mn‐doped CoPS nanowires‐based gold‐silk‐chrysanthemum‐like superstructures arrays on carbon cloth (CC) are developed as electrocatalysts for oxygen evolution reaction (OER), showing Mn‐content ( x %) dependent electrocatalytic performance. Due to the appropriate Mn‐doping‐content and unique superhydrophilic/superaerophobic surface, the Mn‐CoPS‐5%/CC manifests greatly enhanced OER performance with higher turnover frequency and mass activity, outperforming its counterparts, IrO2 /CC, and most of reported OER catalysts.